2022
DOI: 10.21037/jtd-22-1060
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of susceptibility genes and myocardial infarction risk correlation of ischemic cardiomyopathy based on bioinformatics

Abstract: Background: The present study was to investigated differential expressed genes (GEGs) in ischemic cardiomyopathy (ICM), and to construct regulation networks, and to study the correlation between myocardial infarction risk.Methods: Data sets were downloaded from the Gene Expression Omnibus (GEO) to screen out messenger RNA (mRNA) and long non-coding RNA (lncRNA) differentially expressed between ICM samples and normal samples. Gene Ontology (GO) function analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Raw expression data of datasets GSE160516 and GSE61592 were downloaded from the GEO database, and the “limma package” of R software (version 4.0.1) was used to screen differentially expressed genes (DEGs) between reperfusion (myocardial tissue with a reperfusion time of 72 h) and sham myocardium [ 21 ]. The p -value was corrected by the Benjamini–Hochberg method.…”
Section: Methodsmentioning
confidence: 99%
“…Raw expression data of datasets GSE160516 and GSE61592 were downloaded from the GEO database, and the “limma package” of R software (version 4.0.1) was used to screen differentially expressed genes (DEGs) between reperfusion (myocardial tissue with a reperfusion time of 72 h) and sham myocardium [ 21 ]. The p -value was corrected by the Benjamini–Hochberg method.…”
Section: Methodsmentioning
confidence: 99%
“…Experience has shown that bioinformatics technology has great application value in the screening of disease biomarkers, which is of great significance for the diagnosis, treatment, and prognosis of diseases, and can provide a more comprehensive and profound understanding of diseases ( 11 - 14 ). A recent study showed that differentially expressed genes (DEGs) were significantly enriched in metabolic pathways, oxidative phosphorylation, and extracellular matrix (ECM) receptor interactions, and were closely related to fibrosis, collagen catabolic process and inflammatory response function ( 15 ). Interleukin-6 ( IL-6 ) and Ras homologous gene family member A ( RHOA ) may play an important role in the development of ICM, IL-6 and RHOA , however, the value of the IL-6 and RHOA in ICM was poorly studied, further studies are needed to identify new biomarkers in myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic heart disease (IHD) is the leading contributor to the global burden of cardiovascular disease, which is primarily caused by coronary heart disease (CHD) ( 1 , 2 ). In IHD, coronary artery stenosis or occlusion leads to reduced myocardial blood perfusion, resulting in a series of clinical ischemic symptoms ( 3 ). With advancing age, the prevalence of IHD significantly increases, as it is an aging-related disease ( 4 ).…”
Section: Introductionmentioning
confidence: 99%